Is self-publishing a salvation for authors? The case of Lithuanian printed bestseller in the digital environment (Libellarium: journal for research in the field of information and related sciences, 2015)
There has been much speculation in the past years about self-publishing. Some argue that publishing houses do not have a future as publishing service providers. Others claim that it is very easy to publish a book as an e-book. There are many success stories of self-publishers. More and more authors are wondering if they actually need a publisher and a retailer knowing they always take the biggest cut of the pie. The paper looks at the case of a Lithuanian author bestseller (in print). This book has also received the Lithuanian Book of the Year Award in the Fiction category. The author had the book published in Lithuanian by a traditional publishing house. It was quite successful so he decided to self-publish a digital version in English. The steps taken by the author to publish his e-book on Amazon are described and analyzed. Finally, the paper presents the results of selling and promoting his e-book on Amazon platform and provides some insights into facing the market without professional help.
Keywords: self-publishing; e-book; Amazon; Hour of the Wolf